2019
DOI: 10.1038/s41598-019-39093-6
|View full text |Cite
|
Sign up to set email alerts
|

By-Products of Heparin Production Provide a Diverse Source of Heparin-like and Heparan Sulfate Glycosaminoglycans

Abstract: Global production of pharmaceutical heparin (Hp) is increasing, and the production process from raw mucosal material results in large amounts of waste by-products. These contain lower sulfated Hp-like and heparan sulfate (HS), as well as other glycosaminoglycans, which are bioactive entities with pharmaceutical potential. Here we describe the first purification, structural and functional characterisation of Hp-like and HS polysaccharides from the four major by-product fractions of standard heparin production. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…The nonasaccharide #26 lacks 6OS and yet partially promotes FGF2 signaling, demonstrating the utility of complete characterization of sequences by SIMMS 2 in deciphering cues for FGF bioactivities. We then obtained HS byproducts from pharmaceutical heparin production 42 , and used limited heparinase III digestion to produce a range of oligosaccharide size fractions, which were initially separated by size exclusion chromatography (SEC). The dp8 and dp6 fractions were further separated through strong anion exchange (SAX)-HPLC and selected fractions were tested for bioactivity in the BaF3 assay (See Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonasaccharide #26 lacks 6OS and yet partially promotes FGF2 signaling, demonstrating the utility of complete characterization of sequences by SIMMS 2 in deciphering cues for FGF bioactivities. We then obtained HS byproducts from pharmaceutical heparin production 42 , and used limited heparinase III digestion to produce a range of oligosaccharide size fractions, which were initially separated by size exclusion chromatography (SEC). The dp8 and dp6 fractions were further separated through strong anion exchange (SAX)-HPLC and selected fractions were tested for bioactivity in the BaF3 assay (See Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…BaF3 FGF signaling assays. The activity of HS oligosaccharides with FGF1 and FGF2 was determined using BaF3 cells transfected with FGFR1c (from David Ornitz, Washington University, St. Louis) 39,42 . BaF3 cells (1 × 10 4 cells/well) were plated into 96 well plates with recombinant FGF-1 or FGF-2 (1 ng/mL; R&D Systems) and either heparin or oligosaccharides (3 µg/mL).…”
mentioning
confidence: 99%
“…The previous studies confirmed that loss of 6-O-sulfate is associated with the major chemical shift of A-6 and A-5 carbon signals. 47,52 The 13 C spectra comparison of heparin standard and pH 1/ 80 C, indeed, revealed the gradual upfield changes from 69.1 to 62.3 ppm (6.9 ppm) at positions A-6 and downfield move of the A-5 signal, from 71.9 to 74.2 ppm (2.3 ppm). The proton positions of both peaks moved upfield by 0.03 and 0.06 ppm, (Table 3).…”
Section: Nmr Reveals Unexpected Order Of Hydrolysismentioning
confidence: 83%
“…One example is the N-terminus of the cytokine receptor protein CCR5; it needs to be sulfated twice to serve as anchor point for its natural ligand CCL5 and for HIV (Abayev, Rodrigues, Srivastava et al, 2018). Another example is the widely used anti-coagulation medication heparin, a glycosaminoglycan which is known as one of the most highly sulfated biomolecule per weight (Taylor, Hogwood, Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%